Pengembangan Soal Tes Kemampuan Berpikir Kritis Dalam Pelajaran Ilmu Pengetahuan Alam di Sekolah Dasar - Sri Desi Yusnita; Zariul Antosa; Mahmud Alpusari (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
The background of the research is the low critical thinking ability of students. For this reason, the development of test questions based on critical thinking skills in Natural Science learning in Class V Elementary School was carried out. The type of research used is research and development with a 4-D model consisting of define, design, development, and disseminate stages. The feasibility aspect of the test questions was validated by 2 material experts and 1 linguist. The data collection instrument used a questionnaire and test questions. Data analysis using ANATES V4 software with 20 5th grade elementary school students as respondents. The results of material validation obtained a score of 78.59% (very valid) and language validity with a score of 80% (very valid). The results showed that the test questions developed were valid and suitable for use in elementary schools. While the results of practicality show that the test questions have been able to improve students' ability to think critically.